MODERN DENTAL MEDICAL CARE: COMPLETE REHABILITATION OF THE UPPER JAW WITH SUPPORT ON IMPLANTS - Shchepanskyi, Борис (Actual Problems of Medicine and Pharmacy, 2023)
In recent years, clinicians in Ukraine have been working on issues related to the development and implementation of new effective, high-quality, and safe approaches and methods of dispensary examination of the population by conducting regular professional examinations of the oral cavity. Modern systems of early detection of major dental diseases are being implemented. One of the modern methods of restoring a lost tooth or an entire row of teeth is dental implantation by using an implant. An implant is an artificial tooth selected by a doctor considering the characteristics of the patient's jaws; tooth implantation – implantation of an implant in the place of one or more teeth. Implant-supported fixed prosthesis is the best option available to patients for the rehabilitation of edentulous jaws. Immediate loading of a fixed prosthesis significantly improves the quality of life of patients during osseointegration of implants. With a correctly selected treatment plan, the orthodontist can return the patient to a full-fledged life and allow him to smile sincerely (restoration of teeth, satisfactory aesthetics, restoration of chewing function and a good conversational speech), and as a result, an increase in the quality of health and life expectancy.